Comparative Evaluation of Broad Leaf Mustard (BLM) under Different Boron Concentrations in Outdoor Barrel Aquaponics at IAAS, Paklihawa - Gyawali, Sabita; Chaudhary, Prashant; Chaudhary, Mohan; Gurung, Shailesh; Pathak, Rukmagat (International Journal of Applied Sciences and Biotechnology, 2019)
An experiment was conducted at IAAS Paklihawa, Bhairahawa from 6th October 2018 to 15th November 2018 (40 days). An open barrel Aquaponics system with a double factor RCBD type experimental design was used consisting of 3 replications and 2 factors under study. The two factors were boron concentrations (1%, 2% and 3%) and BLM varieties (Marfa Chauda Paat, Manakamana and chinese-430). Marfa Chauda Paat (47.35 gm.) was the highest yielding variety followed by Manakamana (36.42 gm.) and Chinese-430 (26.82 gm.). 1% Boron was found to be the most suitable concentration among the test concentrations for leaf yield. A maximum weight gain of the fish was observed in tank 3 (96.44%) followed by tank 1 (86.26%) and tank 2 (82.18%). An excellent survival percentage of fish was observed as 88.89%, 95.56% and 91.11% in tank 1, 2 and 3 respectively. Similarly, the Average Daily Growth Rate (ADGR) was recorded to be 126.5mg, 91.5mg and 128.25mg in tank 1, 2 and 3 respectively. The Specific Growth Rate (SGR %) was obtained to be 1.26, 1.38 and 1.46 for tank 1, 2 and 3 respectively. Furthermore, final harvest weight of fish was obtained to be 437g, 349.21g and 428.2g in tanks 1, 2 and 3 respectively. Int. J. Appl. Sci. Biotechnol. Vol 7(3): 359-364